(untitled) (The Review of Diabetic Studies, 2024)
Health security has emerged as a critical national and global priority in the wake of recurrent infectious disease outbreaks, pandemics, and evolving public health emergencies. Saudi Arabia, owing to its unique demographic composition, mass gatherings such as Hajj and Umrah, and strategic geopolitical position, faces distinctive health security challenges. This paper examines the current status of health security in Saudi Arabia by analyzing key challenges, national strategies, and the level of system preparedness for emerging health threats. It explores structural, epidemiological, technological, and governance-related dimensions influencing health security, while highlighting the country’s progress under Vision 2030. The study emphasizes surveillance systems, workforce capacity, intersectoral coordination, digital health transformation, and emergency response mechanisms. By critically assessing strengths and gaps, the paper provides policy-oriented recommendations aimed at enhancing resilience, sustainability, and responsiveness of Saudi Arabia’s health security framework. The findings underscore that while Saudi Arabia has made significant strides in strengthening preparedness, continued investment in integrated surveillance, community engagement, research capacity, and regional cooperation remains essential to effectively manage future health threats.